THE SYSTEM OF PATRIOTIC EDUCATION BASED ON THE DEVELOPMENT OF PROFESSIONAL ETHICS OF INTERNAL AFFAIRS OFFICERS IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article explores the theoretical foundations for the development of professional ethics among internal affairs officers, the socio-philosophical aspects of this development, and the prospects for enhancing professional ethics within this field. Additionally, it analyzes the system of patriotic education based on the development of professional ethics among internal affairs officers in New Uzbekistan.